Avaliação do potencial antioxidante do tanino vegetal da Acácia negra em matrizes poliméricas de poliestireno após processo de envelhecimento acelerado - Oliveira, André Luis de (2022)
Nowadays, environmental sustainability is in the focus of the most important topics in materials science, and therefore, bio-based resources have become fundamental for the improvement of materials. When natural components show promising results in the properties under evaluation with performances close to synthetic materials, they represent a great advantage for the environment, especially when resistant to exposure to high levels of ultraviolet radiation and weather conditions. Based on the above, this work aims to evaluate the use of polyphenolic-based plant extracts called “tannins” from the commercially used proanthocyanidin flavonoid family as an antioxidant additive in crystal polystyrene polymer matrices. Polystyrene samples with progressive additions of tannins up to 5% by weight, as well as the control sample, were exposed for three weeks in a photodegradation chamber with UV-C irradiation lamps for the accelerated aging process. During this period, the Spectroscopy technique was performed in the Infrared Region with Fourier Transform and Attenuated Total Reflectance (FTIR-ATR) to monitor the degradation process. Using the carbonyl index calculation technique obtained in the spectrograms of the photodegraded films, changes in the degradation levels of the samples were observed. To complete the study of this work, the samples were also evaluated by the techniques of Spectroscopy in the Visible Ultraviolet Region (UV-Vis) and Contact Angle, which corroborated the results obtained by the FTIR-ATR. Understanding the response of materials when under application requests in aggressive weather situations is extremely important, given that in this study all concentrations of tannins in the mixtures showed an increase in antioxidant activities. The work reached the initial objective in the evaluation of the protective activity of the Black Acacia tannin when incorporated in polymeric matrices, being the sample with 5% of tannin with more expressive values and with antioxidant protection of up to 245%. Future studies will be promising to obtain better answers in the other properties (chemical, physical, thermal and mechanical) for an adequate definition of which concentrations could be the most ideal and effective for certain specific applications.